High resolution hyperpolarized 13C MRSI using SPICE at 9.4T. Issue 2 (8th January 2018) - Lee, Hansol; Song, Jae Eun; Shin, Jaewook; Joe, Eunhae; Joo, Chan Gyu; Choi, Young‐Suk; Song, Ho‐Taek; Kim, Dong‐Hyun
Abstract : Purpose: To test the feasibility of using the SPICE (SPectroscopic Imaging by exploiting spatiospectral CorrElation) technique, which uses the partial separability of spectroscopic data, for high resolution hyperpolarized (HP) 13 C spectroscopic imaging. Methods: Numerical simulations were performed to investigate the impact of transient HP signals on SPICE reconstruction. Furthermore, spectroscopic imaging exams from SPICE and conventional EPSI (echo‐planar spectroscopic imaging) were simulated for comparison. For in vivo experiments, HP 13 C SPICE was performed in a mouse kidney by means of the injection of HP [1‐ 13 C] pyruvate at 9.4T. Results: The variation of lactate/pyruvate from the simulated SPICE was less than 4% under various factors that affect the transient HP signal, suggesting that the impact is negligible. We found that while HP 13 C EPSI was limited to the low signal‐to‐noise ratio (SNR) of lactate, these limitations were mitigated through HP 13 C SPICE, facilitating the improved SNR of lactate and the distinction of tissues. Acquisition of a high resolution HP 13 C spectroscopic image was possible for the in vivo experiments. With the fine structural information, the acquired image showed higher signal of pyruvate and lactate in the renal cortices than in the medullas, which is known to be attributed to higher activity of lactate dehydrogenase. Conclusion: The feasibility of HP 13 C SPICE was investigated. Simulation studies were conducted and in vivo experiments were performed in the mouse kidney at 9.4T. Results confirmed that a high resolution HP 13 C spectroscopic image with adequate spectral resolution can be obtained. Magn Reson Med 80:703–710, 2018. © 2018 International Society for Magnetic Resonance in Medicine.